Inlay-Retained Fixed Dental Prosthesis: A Clinical Option Using Monolithic Zirconia - Davide Augusti; Gabriele Augusti; Andrea Borgonovo; Massimo Amato; Dino Re (Hindawi Limited, 2014)
Different indirect restorations to replace a single missing tooth in the posterior region are available in dentistry: traditional full-coverage fixed dental prostheses (FDPs), implant-supported crowns (ISC), and inlay-retained FDPs (IRFDP). Resin bonded FDPs represent a minimally invasive procedure; preexisting fillings can minimize tooth structure removal and give retention to the IRFDP, transforming it into an ultraconservative option. New high strength zirconia ceramics, with their stiffness and high mechanical properties, could be considered a right choice for an IRFDP rehabilitation. The case report presented describes an IRFDP treatment using a CAD/CAM monolithic zirconia IRFDP; clinical and laboratory steps are illustrated, according to the most recent scientific protocols. Adhesive procedures are focused on the Y-TZP and tooth substrate conditioning methods. Nice esthetic and functional integration of indirect restoration at two-year follow-up confirmed the success of this conservative approach.